KOMPETENSI PENYULUH PERTANIAN TERHADAP PEMBERDAYAAN KELOMPOK WANITA TANI DI KECAMATAN SINJAI UTARA KABUPATEN SINJAI - Wahyuni, Yuyun Amara; Megawati, Megawati; Nurdin, Fadilah (Jurnal Riset Multidisiplin Agrisosco, 2025)
The low motivation and participation of members of the Women Farmers Group (KWT) is thought to be related to an extension approach that has not been optimal in empowering members. This study aims to analyze the influence of agricultural extension workers' competence on the empowerment of KWT, which includes aspects of knowledge, attitude, skills, and work experience. The method used in this study was quantitative. Data processing techniques used descriptive analysis and multiple linear regression analysis. The results of the study simultaneously showed that extension worker competence (knowledge, attitude, skills, and work experience) had a positive and significant effect on KWT empowerment. Partially, knowledge competence was the most dominant variable. The coefficient of determination ($R^2$) value obtained was 73.5%, indicating that the four independent variables together influence the dependent variable of empowerment, while the remaining 26.5% is influenced by other factors or variables not examined in this study